Development of an Android-Based Physical Education Teacher Performance Monitoring System in Tegal Regency - sandi kurniawan (Journal of Physical Education and Sports, 2026)
This study was motivated by the results of a questionnaire distributed to the Physical Education Teachers’ Working Group in Tegal Regency regarding the organizational management of the KKG PENJAS. The findings revealed that there is currently no comprehensive, integrated digital-based monitoring system; instead, conventional methods such as physical record-keeping and informal communication are still used during every KKG PENJAS meeting in Tegal Regency. Based on this phenomenon, an Android-based monitoring system could serve as an innovation and solution to address this issue, thereby simplifying and supporting the management process of the KKG PENJAS organization. This study aims to develop an Android-based monitoring system for the integrated, real-time management of the KKG PENJAS organization. The research method employed is Research and Development (R&D) using the Borg & Gall development model, which has been modified or simplified to account for various factors, ensuring effective and efficient implementation. The stages include: Research and Information Collection, Product Development, and Product Testing and Evaluation. The subjects of the study were media experts, subject matter experts, and the KKG PENJAS of Tegal Regency. The data collection instruments used were feasibility and effectiveness questionnaires. The research sample was determined using the Purposive Sampling technique within the KKG PENJAS of Tegal Regency. The research results are as follows: The validation results from Media Expert 1 and Media Expert 2, based on the application’s visual design and programming aspects—which received scores of 94% and 88%, respectively—were categorized as “highly feasible or highly valid.” Subsequently, a small-scale pilot test involving 15 teachers yielded a 90% rating in the “highly feasible or highly valid” category, and a large-scale pilot test involving 50 teachers yielded a 95% rating in the “highly feasible or highly valid” category. Based on these results, it has been demonstrated that this Android-based monitoring system is highly feasible for use by the Physical Education Teachers’ Working Group in Tegal Regency